Pengendalian Aplikasi Finance and Billing Management System (FBMS) Terhadap Piutang Usaha Pada Kantor Pelabuhan Laut Batam - Joni Pranata (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2014)
This thesis carried out at the office of PelabuhanLaut Batam. Office Seaport Batam is a company engaged in shipping services and take services on credit policy, with the number of subscribers of approximately 405 customers. Management of accounts receivable in the Office of Batam Sea port using an accounting application that is an application Finance And Billing Management System. Problems often occur, errors both in nominal and receivables recording data input to a system, customers who paid off their debt still not paid off recorded in the system, and the frequent occurrence of trade receivables nominal difference in the nominal ledger accounts receivable in the accounts receivable ledger. The purpose of this study was to determine how the finance application control and billing management system to the accounts receivable of the company. Data collection techniques used were interviews and observation. Data analysis methods that I use in this research is descriptive analysis. Based on the results of this study the authors can draw the conclusion that the application control is applied to the Office of the Port of Batam is quite good although there are several kinds of controls have not been implemented